Dynamics Performance Test for UTY Passenger Electric Locomotive - 陈国胜; 储高峰 (机车电传动)
Technic characteristic and technic parameter of the bogie for UTY passenger locomotive were introduced, and the test results on the safety, dynamic characteristic and the stability of the locomotive was analyzed. The results showed that with the drive unit using flexible suspension, the dynamics performance indexes of the locomotive met the designing requirement, especially the good transverse performance.